Principles of anatomy and physiology - Tortora, Gerard J.; Grabowski, Sandra Reynolds (New York : John Wiley & Son, Inc., 2000)
Student CD-ROM includes interactive activities, tests, and special features (including audio pronunciation glossary) to help students enhance their understanding of anatomy and physiology.
v. 1. Organization of the human body -- v. 2. Support and movement -- v. 3. Control systems of the human body -- v. 4. Maintenance and continuity of the human body.
Includes index.
Keywords: HUMAN PHYSIOLOGY